Determinant analysis of MSMEs credit in Indonesia - P Prasetiono; Anisa Puspa Dina (Department of Management | Faculty of Economics and Business | Universitas Diponegoro, 2020)
This study was conducted to analyze several variables as the determinants of credit of micro, small, and medium enterprises (MSME) in Indonesia. Those variables are society income, geographic branch penetration (GBP), demographic branch penetration (DBP), credit account per capita (CAC), and deposit account per capita (DAC) of commercial banks. The samples used in this study are 33 Provinces in Indonesia in the period 2013-2017 using the purposive sampling technique. We examined data uses the non-participant observation method by directly quoting financial, GRDP, banking, geographical, and demographic data. The analysis used in this research is multiple linear regression consisting of the classic assumption test, F test, t-test, and hypothesis testing. This study indicated that society income, CAC, and DBP have a positive and significant effect on MSME credit. In contrast, GBP has a positive but non-significant effect on MSME credit, and DBP has a significant negative effect on MSME credit.